Teacher's Creativity In Arranging Ensemble Music In Junior High School (SMP) In Purbalingga Regency (Jurnal Seni Musik, 2021)
Teachers play an important and strategic role as the center of learning resources for the students. A teacher needs to develop the form of musical creativity as much as possible so that it will help the learning process go well, and result in students succeed in achieving their learning objectives. Therefore, this study focuses on the teacher’s creativity on (1) the making concept of the ensemble music arrangement in junior high school in Purbalingga Regency, (2) the creation process of the ensemble music arrangement of a medium in junior high school in Purbalingga Regency. The research method used in this study is qualitative with descriptive exposure. The research subjects were music teachers in Purbalingga Regency. Data collection is carried out with observation, interview, and documentation. Data analysis techniques are divided into three stages, namely data reduction, data presentation, and concluding. The results of interviews and observations that have been collected are included in the documentation, images, photographs, field notes, personal records, and other documents after being studied, then reduced into an abstraction.